Multiple Gene Deletion Mutants of Equine Herpesvirus 1 Exhibit Strong Protective Efficacy Against Wild Virus Challenge in a Murine Model - Stephanie S. Pradhan; Vekataramireddy Balena; Bidhan Chandra Bera; Taruna Anand; Rhushikesh Khetmalis; Aashwina Madhwal; Supriya Kandasamy; Selvaraj Pavulraj; Manju Bernela; Priya Mor; Bhupendra Nath Tripathi; Nitin Virmani (Vaccines)
Background: Equine herpesvirus type 1 (EHV1) is a ubiquitous viral pathogen infecting the equine population worldwide. EHV1 infection causes respiratory illness, abortion, neonatal foal mortality, and myeloencephalopathy. The currently available modified live EHV1 vaccines have safety and efficacy limitations. The two mutant EHV1 viruses (vToH-DMV (∆IR6/gE) and vToH-QMV (∆IR6/UL43/gE/UL56)), generated by the deletion of genes responsible for virulence (gE and IR6) and immunosuppression (uL43 and uL56), have been previously characterized by our group and found to generate good immune responses. The present study aimed to determine the safety and protective efficacy of the above mutants against a virulent EHV1 challenge in a murine model. Methods: BALB/c mice were intranasally immunized with a live vToH-QMV or vToH-DMV vaccine. Intranasal booster immunization was given at 14 days post-vaccination (dpv). Both mutants induced an optimal level of EHV1-specific humoral and cell-mediated immune responses, as determined by virus neutralization assay, ELISA, and immunophenotyping. At 35 dpv, the mice were intranasally challenged with wild-type EHV1 (vRaj strain). Results: Amongst the two mutants, vToH-QMV induced a better immune response than the vToH-DMV vaccine. Furthermore, vToH-QMV provided good protection in mice against the virulent challenge. It specifically exhibited less severe clinical disease in terms of clinical signs, body weight reduction, and gross and histopathological lung lesions accompanied by early virus clearance. Conclusions: These studies are suggestive of vToH-QMV EHV1 being a potential vaccine candidate against EHV1 infection, which needs to be finally tested in the main host, i.e., horses.